Long-term complete remission with immunotherapy in advanced RET fusion-positive NSCLC with brain metastases: a case report and literature review - Shang, Shuheng; Qin, Meng; Zhang, Shuangmei (Frontiers in Oncology, 2025)
The rearranged during transfection (RET) fusion is a rare genetic alteration in non-small-cell lung cancer (NSCLC), and the presence of brain metastases significantly influences prognosis. We present a 59-year-old patient diagnosed with RET fusion-positive lung adenocarcinoma which had metastasized to the brain at the time of initial diagnosis, classified as stage IVB, cT3N3M1. Tumor biopsy immunohistochemistry showed PD-L1 positivity (10%). After three cycles of pemetrexed plus cisplatin (PC) regimen combined with camrelizumab (a PD-1 inhibitor), a partial response (PR) was observed through chest computed tomography (CT) and brain magnetic resonance imaging (MRI). The patient underwent whole brain radiotherapy (WBRT) with a total dose of 37.5 Gy over 15 fractions, followed by 3 cycles of the PC regimen plus camrelizumab. Complete remission (CR) was achieved during 30 months of maintenance therapy with pemetrexed plus camrelizumab. The most recent follow-up was in February 2025. Both chest CT and brain MRI continued to show CR, with no clear indications of metastases. During the course of immunochemotherapy, grade 1 bone marrow suppression, but no toxicity of grade 3 or above, was observed. NSCLC patients who have PD-L1 overexpression and RET fusion-positivity may respond well to immunotherapy. Combining radiotherapy with immunotherapy may enhance local control of brain metastases.